An Evaluation of a Commercialized mHealth Intervention to Promote Physical Activity in the Workplace - Di Sebastiano, Katie M.; Lau, Erica Y.; Yun, Lira; Faulkner, Guy (Frontiers in Public Health, 2022)
Background UPnGO with ParticipACTION (UPnGO) was a commercialized 12-month workplace physical activity intervention, aimed at encouraging employees to sit less and move more at work. Its design took advantage of the ubiquitous nature of mobile fitness trackers and aimed to be implemented in any office-based workplace in Canada. The program was available at cost from June 2017 to April 2020. The objectives of this study are to evaluate the program and identify key lessons from the commercialization of UPnGO. Methods Using a quasi-experimental design over 3 time points: baseline, 6 months, 12 months, five evaluation indicators were measured as guided by the RE-AIM framework. Reach was defined as the number and percentage of employees who registered for UPnGO and the number and percentage of sedentary participants registered. Effectiveness was assessed through average daily step count. Adoption was determined by workplace champion and senior leadership responses to the off-platform survey. Implementation was assessed as the percentage of participants who engaged with specific program elements at the 3-evaluation time points. Maintenance was assessed by the number of companies who renewed their contracts for UPnGO. Results Reach across 17 organizations, 1980 employees participated in UPnGO, with 27% of participants identified as sedentary at baseline. Effectiveness Daily step count declined from 7,116 ± 3,558 steps at baseline to 6,969 ± 6,702 (p = <0.001) at 12 months. Adoption Workplace champion and senior leadership engagement declined from 189 to 21 and 106 to 5 from baseline to 12 months, respectively. Maintenance Two companies renewed their contracts beyond the first year. Conclusions The commercialization of UPnGO was an ambitious initiative that met with limited success; however, some key lessons can be generated from the attempt. The workplace remains an important environment for PA interventions but effective mHealth PA programs may be difficult to implement and sustain long-term.